Government Project Failure in Developing Healthcare Website – A Review with Particular Reference to PMBOK - Selvaraj, Katyaayani; Hanie Umi Sofea Mohamad Nizam; Muhammad Firdaus Mohd Sapri; Nurhafizah Azmy; Megat Haziq Megat Azahari; Mohamad Aizi Salamat (Applied Information Technology And Computer Science, 2023)
This article provides an overview of incidents and issues related to project management in the development, operation, and upkeep of HealthCare.gov, the United States’ official health system’s government. It was launched under the Affordable Care Act, and has faced countless project management issues since its inception in 2013. This study focuses on the aspects that contribute to the failure of e-government project. It investigates the background of project failure in the framework of the project management body of knowledge. The incidents discussed in this report encompass a few aspects of incident that happened such as cost management, risk management, scope management, human resources management, communication management, and general project management practices. Each of the incidents has been analyzed with full focus on understanding its greater impact and big implications for the project, as well as identifying the strategies by a project manager for locating such challenges that caused these incidents. By examining these incidents, this report aims to provide insights into the complexity and importance of effective project management in large-scale, critical systems like HealthCare.gov.